Adepamycin: design, synthesis and biological properties of a new peptide with antimicrobial properties - Almeida, Luis Henrique de Oliveira; Oliveira, Caio Fernando Ramalh de; Rodrigues, Mayara de Souza; Neto, Simone Maria; Boleti, Ana Paula de Araujo; Taveira, Gabriel Bonan; Mello, Erica de Oliveira; Gomes, Valdirene Moreira; Santos, Edson Luca dos; Crusca Jr, Edson [UNESP]; Franco, Octavio Luiz; Cardoso, Marlon Henrique e Silva; et al. (Elsevier B.V., 2020)
Antimicrobial peptides (AMP) are molecules with a broad spectrum of activities that have been identified in most living organisms. In addition, synthetic AMPs designed from natural polypeptides have been largely investigated. Here, we designed a novel AMP using the amino acid sequence of a plant trypsin inhibitor from Adenanthera pavonina seeds (ApTI) as a template. The 176 amino acid residues ApTI sequence was cleaved in silico using the Collection of Antimicrobial Peptides (CAMPR3), through the sliding-window method. Further improvements in AMP structure were carried out, resulting in adepamycin, an AMP designed from ApTI. Adepamycin showed antimicrobial activity from 0.9 to 3.6 mu M against Escherichia coli, Klebsiella oxytoca, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus strains. Moreover, this peptide also displayed activity against Candida albicans and Candida tropicalis. No toxic effects were observed on healthy human cells. Studies on the mechanism of action of adepamycin were carried out using an E. coli and C. tropicalis. Adepamycin triggers membrane disturbances, leading to intracellular nucleic acids release in E. coli. For C. tropicalis, an initial interference with the plasma membrane integrity is followed by the formation of intracellular reactive oxygen species (ROS), leading to apoptosis. Structurally, adepamycin was submitted to circular dichroism spectroscopy, molecular modeling and molecular dynamics simulations, revealing an environment dependent alpha-helical structure in the presence of 2,2,2- trifluoroethanol (TFE) and in contact with mimetic vesicles/membranes. Therefore, adepamycin represents a novel lytic AMP with dual antibacterial and antifungal properties.
Keywords: Rational design; Antimicrobial peptides; Pathogenic bacteria; Pathogenic yeast